Navigating Qiwamah: insight into work-family interactions among Muslim women in Malaysia - Ghalia, Bouhedda; Subhani, Zulqernain Haider (Contemporary Fiqh Research Unit (CFRU), IIUM and Islamic Book Trust, 2025)
Qiwamah, a foundational principle in Islamic discourse, has garnered significant attention for its role in the financial and institutional management of family life within Muslim communities. The principle of Qiwamah does not merely relate to the husband’s responsibility of providing maintenance; instead, it is a broad concept that provides a systematic and proper mechanism for family institutions, encompassing the husband’s responsibilities in maintenance, well-being, safety, and the and the moral and spiritual development of the wife and family members. However, it also entails the wife’s obedience and subordination to her husband. Qiwamah has special effects on maintenance anddivorce in the context of family. However, in the contemporary landscape, where work and family spheres are distinctly segregated, a critical examination of Qiwamah’s relevance and application to the work-family interface of Muslim women becomes imperative. This study adopts a content analysis method to systematically explore the multifaceted implications of Qiwamah on the workfamily dynamics of Muslim women in Malaysia. Central to this exploration is the issue of work-family segregation, broadly associated with the notion of Qiwamah. The research delves into the issue of work-family segregation in the context of Qiwamah. In the context of Muslim women’s work-family interface, the study also explores the issue of men’s dominance over women and the potential for women to become supervisors or in charge of men at the workplace, with a particular focus on how modern societies are redefining these traditional roles and responsibilities. Through this comprehensive analysis, the study aims to offer insightful perspectives on the intersectionality of Islamic principles, gender roles, and the evolving demands of work and family life. It seeks to contribute to a deeper understanding of how Muslim women navigate their professional and personal spheres within the framework of Qiwamah, shedding light on the potential for reinterpreting traditional roles in the context of contemporary societal norms and expectations.